INTERLINGUAL ERRORS AND INTRALINGUAL ERRORS FOUND IN NARRATIVE TEXT WRITTEN BY EFL STUDENTS IN LAMPUNG - Eny Maulita Purnama Sari (Universitas Muhammadiyah Surakarta, 2016)
The current study investigates the interference of L1 (Indonesian) into L2 (English) and the errors that occur due to the influence of TL (target language). The focus of the study is on the errors committed by these EFL students in writing narrative text and emphasized on interlingual errors and intralingual errors. The objectives of the study are to investigate the errors committed by these EFL students in order to findout; (1) the types of interlingual errors and intralingual errors in Junior High School, Senior High School and University, (2) the frequencies of interlingual errors and intralingual errors in Junior High School, Senior High School and University, and (3) the similarities and differences of interlingual errors and intralingual errors in Junior High School, Senior High School and niversity. The researcher used Qualitative descriptive as the method design and writing test as the data collecting technique. The data was erroneous sentences found in the students’ narrative writing. The subjects of the study comprised 30 eight grade of SMP Muhammadiyah Pekalongan, East Lampung and 30 eleven grade SMKN 1 Pekalongan, East Lampung, and 30 fourth-year students of English Department of University of Muhammadiyah, Metro Lampung. The findings of the study suggest: (1) The types of interlingual errors andintralingual errors made by SMP, SMK and University students divided into 2 levels, they are morphological level and syntactical level. (2) the frequent of interlingual errors in Junior High School 36 cases (30.26%), in Vocation High School 39 cases (36.77%) and 9 cases (10.98%) in University. The frequent of intralingual errors in Junior High School 83 cases (69.74%), in Senior High School 70 cases (64.23%) and 73 cases (89.02%) in University, and (3) The similarities of interlingual errors and intralingual errors found in Junior High School, Vocation High School and University are 2 types. In morphological level, they are the use of L1 structures and omission of BE in nominal sentences. There are also 2 types in syntactical level, they are the use of present BE in past event and the use of present Verb in past event. The differencesof interlingual errors and intralingual errors found in SMP, SMK and University are (1) in SMP there are 8 types errors that found in the students’ writing, (2) 3 types of errors in SMK, and (3) 2 types of errors found in University.